The 20th anniversary of the department of transport technological equipment of the Vilnius Gediminas technical university - Bogdevičius, Marijonas; Spruogis, Bronislovas; Sivilevičius, Henrikas; Bartulis, Vilius; Jurevičius, Jurgis; Prentkovskis, Olegas; Sokolovskij, Edgar; Vladimirov, Oleg; Suslavičius, Vladimiras; Junevičius, Raimundas; Karalevičius, Irmantas; Vika, Aleksandr; et al. (Transport, 2006)
"The 20th anniversary of the department of transport technological equipment of the Vilnius Gediminas technical university" Transport, 11(1),  p. 1-8First published online: 27 Oct 2010